Curriculum and Pedagogy of Alternation: an experience of the Forest School in Rio Branco, Acre - Letícia Mendonça Lopes Ribeiro; Adriana Ramos dos Santos (Universidade Federal do Norte do Tocantins, 2019)
The objective is to present the experience of the Alternation Pedagogy in Centers of Technical Vocational Education of secondary level, highlighting the history and the curricular practices of the "Roberval Cardoso Vocational and Technological Training Center", the "Escola da Floresta", in Rio Branco, Acre. A brief literature review was chosen with historical passages of the constitution of the Escola da Floresta (Peneireiro, 2013; Montysuma, 2017) and questions about the curriculum in Alternation Pedagogy, with emphasis on the referred school (Acre, 2011; 2012). The Escola da Floresta is recognized as an institution representative of the Alternation system, based on the precepts of sustainability, Amazonian valorization and the appropriate use of forest resources. Despite having as its educational pillar the neoliberal Curriculum for Skills, the specific case of Escola da Floresta manages to be a successful example of the Pedagogy of Alternation and the exercise of dialogue between social and individual issues that permeate the peasant context, especially in interactions, between learners and learning mediators. It is concluded that it is essential to think (and enable) the training of professionals who will work in the Acre forest in a conjuncture that refutes the training and urban-centric education and values ​​the peasant identity.